Orchidaceae endémicas del Perú - Roque, José (2006)
Orchids are the most diverse plant family in the Peruvian flora, with approximately 212 genera and 2020 species registered to date (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004). Estimates of Peru’s total orchid diversity fluctuate between 2500 and 3500 species (Collantes, pers. comm.). Most Peruvian orchids are epiphytic or terrestrial herbs, and in many cases both habits may be found in a species. Here we recognize 775 endemic species in 137 genera, making the Orchidaceae one of the most important families for Peru’s endemic flora. Endemic taxa have been found in several ecological regions, but mainly in Very Humid Montane Forests, Very Humid Lowland Forests, and Mesoandean regions, between 100 and 4600 m elevation. Habitat destruction and illegal extraction and illegal commerce of wild plants make these taxa particularly threatened. One hundred and five orchid species endemic to Peru have been reported to date from the country’s system of protected areas.